The Influence of Study Room Facilities on Students’ Learning Motivation - Elviana, Elviana; Syamsuria, Syamsuria; Basri, Basri (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The aim of the author in conducting this research is to find out that study room facilities play a role in efforts to increase students' learning motivation, as well as provide valuable input to the school, especially XI IPS SMA Negeri 16 Bone, that student study room facilities can influence students' enthusiasm and motivation for learning. , and to gain practical experience with scientific research fields that can be contributed to the world of education in particular. The variables in this research consist of dependent variables (free variables) and independent variables (dependent variables). The influence of learning facilities is the independent variable with the symbol X. Learning motivation is the dependent variable with the symbol Y. This research is ex post facto research which is correlational in nature. The method in this research is ex post facto with a quantitative approach. The population in this research is Class The total number of students is determined using the Regression Test formula. The data collection technique uses a questionnaire, learning space facilities at school, and student learning motivation. Research data analysis uses simple linear regression. Based on the calculation results of this research using a simple regression test, it shows that: there is a positive and significant influence of learning facilities on student learning motivation in economics subjects for class XI IPS students at SMA Negeri 16 Bone, proven by looking at the simple regression data analysis. This is proven when the value with a value of 30, the value obtained is Y = 137.24, which is greater than the F table value = 3.94. Meanwhile, when predicting 16 Bone.